Amplification of Australian Heatwaves via Local Land‐Atmosphere Coupling. Issue 24 (16th December 2019) - Hirsch, Annette L.; Evans, Jason P.; Di Virgilio, Giovanni; Perkins‐Kirkpatrick, Sarah E.; Argüeso, Daniel; Pitman, Andrew J.; Carouge, Claire C.; Kala, Jatin; Andrys, Julia; Petrelli, Paola; Rockel, Burkhardt
Key Points: Spatial variability in the land‐atmosphere coupling defines local heatwave sensitivity to antecedent land surface conditions Land‐driven coupling regions experience a higher heatwave day frequency with temperatures sensitive to prior soil moisture conditions Antecedent soil moisture anomaly rather than drying rate 2 weeks prior to a heatwave has a longer impact on heatwave temperatures Abstract: Antecedent land surface conditions play a role in the amplification of temperature anomalies experienced during heatwaves by modifying the local partitioning of available energy between sensible and latent heating. Most existing analyses of heatwave amplification from soil moisture anomalies have focused on exceptionally rare events and consider seasonal scale timescales. However, it is not known how much the daily evolution of land surface conditions, both before and during a heatwave, contributes to the intensity and frequency of these extremes. We examine how the daily evolution of land surface conditions preceding a heatwave event contributes to heatwave intensity. We also diagnose why the land surface contribution to Australian heatwaves is not homogeneous due to spatiotemporal variations in land‐atmosphere coupling. We identify two coupling regimes: a land‐driven regime where surface temperatures are sensitive to local variations in sensible heating and an atmosphere‐driven regime where this is not the case. Northern Australia is consistently strongly coupled, where antecedent soil moisture conditions can influence temperature anomalies up to day 4 of a heatwave. For southern Australia, heatwave temperature anomalies are not influenced by antecedent soil moisture conditions due to an atmosphere‐driven coupling regime. Therefore, antecedent land surface conditions have a role in increasing the temperature anomalies experienced during a heatwave only over regions with strong land‐driven coupling. The timescales over which antecedent land surface conditions contribute to Australian heatwaves also vary regionally. Overall, the spatiotemporal variations of land‐atmosphere interactions help determine where and when antecedent land surface conditions contribute to Australian heat extremes. Plain Language Summary: Research focused on the Northern Hemisphere has demonstrated that unusually dry soils preceding a heatwave event amplify the hot conditions experienced. However, we do not know whether the daily evolution of how the land surface dries out can amplify heatwave temperatures or whether any impact is similar across a large area like Australia. In exploring these knowledge gaps, we find that regions where there is a larger drying trend tend to be more sensitive to land water availability and have more heatwave days. We find that the effect of dry soils before a heatwave varies considerably across Australia. Identifying where dry soils have a large impact on heatwaves required classifying the land into regions where soil water variability affects surface temperatures and where it does not. This could be extended to other atmospheric processes to differentiate between local and remote influences.